LES ECOSYSTEMES DOMESTIQUES PAR LHOMME DANS LANCIEN ROYAUME INSANA - TIMOR - WALUJO, EKO BAROTO (REINWARDTIA, 2000)
Based on ethnobotanical data, agricultural practice and floristic analysis (simple and transect analysis), the author tries to evaluate human impact on vegetation cover. He attempts also to show that originally this environment consisted of two different types i.e. dry and humid, each of which corresponded to a certain floristic composition. There is a tendency for this difference in composition to decrease there where human interference is strongest,i.e. on land under cultivation. It is difficult to verify that there is any part of Insana that is not influenced directly or indirectly by human intervention. It is evident that the practice of slash and burn has had the strongest influence on the transformation of the vegetation cover.However, we have to consider also that the introduction of Bah cattle to this territory has had a great impact on the modification of the environment. Meanwhile there is a tendency to increase the number of species or varieties of economic plants, in particular food plants.